Oncosexology – selected issues taking into account the problem of sexological care of patients with cancer - Katarzyna Plagens-Rotman; Piotr Merks; Magdalena Pisarska-Krawczyk; Ewa Jakubek; Małgorzata Mizgier; Justyna Jaskulska; Małgorzata Wójcik; Urszula Religioni; Grażyna Jarząbek-Bielecka; Witold Kędzia (Menopause Review)
As can be seen from research, 44% of oncological problems disclose problems in relationships with a partner. About 80% of oncological patients report deterioration of the quality of their sexual life. Although the situation improves, a significant majority of ill persons do not obtain assistance in the scope of sexuality during oncological treatment. Intimacy is an important sphere of life and can support the process of recovery. Intimacy plays special role in the difficult period of the fight against disease. Independently of the applied method of oncological treatment, side effects of therapy can influence one’s sexual life. This means that an increasing number of persons who are healed from cancerous disease are exposed to the long-term undesirable influence of treatment. The process of oncological treatment has an essential impact on the intimate life of those who suffer from oncological diseases. To a great extent, this process and the disease itself contribute to a decrease of the quality of life due to the appearance of symptoms caused by earlier menopause, they negatively influence the feeling desire and sexual performance. Unfortunately, despite the development of oncosexology, sexual problems of oncologically ill persons are not noticed, and sometimes they are played down or overlooked due to everyday problems.